Brain Connectometry Changes in Space Travelers After Long-Duration Spaceflight - Doroshin, Andrei; Jillings, Steven; Jeurissen, Ben; Tomilovskaya, Elena; Pechenkova, Ekaterina; Nosikova, Inna; Rumshiskaya, Alena; Litvinova, Liudmila; Rukavishnikov, Ilya; De Laet, Chloë; Schoenmaekers, Catho; Sijbers, Jan; et al. (Frontiers in Neural Circuits, 2022)
Humans undergo extreme physiological changes when subjected to long periods of weightlessness, and as we continue to become a space-faring species, it is imperative that we fully understand the physiological changes that occur in the human body, including the brain. In this study, we present findings of brain structural changes associated with long-duration spaceflight based on diffusion magnetic resonance imaging (dMRI) data. Twelve cosmonauts who spent an average of six months aboard the International Space Station (ISS) were scanned in an MRI scanner pre-flight, ten days after flight, and at a follow-up time point seven months after flight. We performed differential tractography, a technique that confines white matter fiber tracking to voxels showing microstructural changes. We found significant microstructural changes in several large white matter tracts, such as the corpus callosum, arcuate fasciculus, corticospinal, corticostriatal, and cerebellar tracts. This is the first paper to use fiber tractography to investigate which specific tracts exhibit structural changes after long-duration spaceflight and may direct future research to investigate brain functional and behavioral changes associated with these white matter pathways.